Facile synthesis of ternary CdMnS QD-based hollow nanospheres as fluorescent/magnetic probes for bioimaging. Issue 7 (15th January 2016) - Zhao, Bingxia; Huang, Peng; Rong, Pengfei; Wang, Yu; Gao, Mengyu; Huang, Haiyan; Sun, Kang; Chen, Xiaoyuan; Li, Wanwan
Abstract : Fluorescent/magnetic dual-functional CdMnS hollow nanospheres with bright tunable emission and strong MR signal were synthesized via a facile Ostwald-ripening process with promising applications in bioimaging. Abstract : In this study, fluorescent/magnetic dual-functional hollow nanospheres conducted by ternary CdMnS nanoparticles were synthesized via a facile Ostwald-ripening process. The as-prepared hollow nanospheres exhibited bright and tunable emission under excitation with a 365 nm UV light coupled with a strong MR signal, suggesting their promising applications in bioimaging.